URGENSI ETIKA PROFESI HUKUM SEBAGAI UPAYA PENEGAKAN HUKUM YANG BERKEADILAN DI INDONESIA - Tardjono, Heriyono (Universitas Muhammadiyah Palembang, 2021)
Ethics are ideas, ideals about human desires, behavior or human behavior, ethics always provides good examples. In ethics, it is discussed and analyzed central themes such as conscience, freedom, responsibility, norms, rights, obligations, and virtues. One aspect of ethics that is highlighted with regard to a person's behavior is in a field of work or expertise called a profession. Ethics in the legal profession has a very important role in realizing the achievement of just law enforcement. So that ethics in the legal profession (professional code of ethics) is an integral part of the behavior of law enforcers as a form of just law enforcement.Keywords: ethics, legal profession, justice.